miR-12 and miR-124 contribute to defined early phases of long-lasting and transient memory - Julia Michely (Nature Portfolio, 2017)
Abstract MicroRNAs (miRNAs) are important epigenetic regulators of mRNA translation implicated in long-lasting synaptic plasticity and long-term memory (LTM). Since recent findings demonstrated a role of epigenetic regulation of gene expression in early memory phases we investigated whether epigenetic regulation by miRNAs also contributes to early memory phases. We used the olfactory associative learning paradigm in honeybees and addressed the contribution of miRNAs depending on the conditioning strength. We selected miR-12, miR-124, and miR-125 that have been implicated in processes of neuronal plasticity and analysed their contribution to non-associative and associative learning using miRNA inhibitors. Blocking miR-12, miR-124, or miR125 neither affects gustatory sensitivity nor habituation nor sensitization. Blocking the function of miR-12 and miR-124 during and shortly after 3-trial conditioning impairs different early memory phases. Although different, the function of miR-12 and miR-124 is also required for early phases of transient memory that is induced by 1-trial conditioning. Blocking miR-125 has no effect on early memory independent of the conditioning strength. These findings demonstrate that distinct miRNAs contribute to early phases of both, transient memories as well as long-lasting memories.